LEVERAGING PRODUCT INNOVATION AND DIGITAL PROMOTION: A STRATEGY FOR SALES GROWTH IN THE MY KLAMBI FASHION BRAND - Nanda Nugraha; Defrizal Defrizal (ZILLZELL MEDIA PRIMA, 2026)
This study aims to examine the influence of product innovation and digital promotion on the sales performance of My Klambi, a local modest fashion brand in Indonesia. It seeks to determine the individual and combined effects of these strategies in addressing the brand’s seasonal sales dependency. A quantitative approach was employed, using a survey of 100 active My Klambi resellers selected via purposive sampling. Data were collected through a structured online questionnaire measuring perceptions of product innovation, digital promotion, and sales performance using a 4-point Likert scale. Multiple linear regression analysis was conducted using SPSS to test the hypotheses. The results indicate that product innovation has a strong, positive, and significant effect on sales performance (β = 0.677, p = 0.000). In contrast, digital promotion has a positive but statistically non-significant direct effect (p = 0.080). However, both variables together exert a significant synergistic influence on sales performance (F = 104.005, p = 0.000), explaining 68.2% of its variance. For My Klambi, sustaining product innovation is paramount for direct sales growth. Digital promotion should be optimized as a supportive tool for brand building, lead generation, and amplifying innovation narratives. Management should develop integrated campaigns that leverage the synergy between innovative products and targeted digital storytelling to reduce seasonal reliance and ensure year-round sales stability. This study contributes to the marketing literature by empirically testing the product-promotion nexus within the underexplored context of a modest fashion SME in an emerging market. It reveals the nuanced, synergistic rather than purely direct, role of digital promotion in a reseller-based business model, offering contextual insights for similar firms.